Crack Behaviour of Polypropylene Fiber Reinforced Concrete - Md Esak, Nuraisyah Amirah; Ayop, Sallehuddin Shah (Recent Trends in Civil Engineering and Built Environment, 2026)
Polypropylene fiber reinforced concrete has emerged as a promising solution to enhance the crack resistance and overall mechanical properties of concrete. Cracks in concrete structures can compromise their structural integrity, durability, and, serviceability. Therefore, it is crucial to understand and mitigate the crack behaviour in concrete to ensure the long-term performance of structures. This study aimed to determine the effect of crack behaviour and evaluate the flexural strength of reinforced concrete with different percentage of PP fiber. 12 concrete beam specimens with dimensions of 150 mm width, 150 mm height and 600 mm length were manufactured and tested. The test examined concrete samples with varying percentages of polypropylene fiber 1.0%, 1.5%, and 2.0%, while maintaining a constant water-to-cement (w/c) ratio of 0.5. The concrete specimens were tested for flexural strength at 28 days. Based on the result that obtained from flexural strength test, concrete beam that contained 1.5% of PP fiber is the optimum strength for this experiment. The experiment validates the hypothesis that fiber reinforcement can enhance the material's structural performance by showing the beneficial effects of PP fibers on concrete's flexural strength.